The sextech industry and innovative devices for treating sexual dysfunction - Varod, Shelly; Heruti, Rafi J. (International journal of impotence research, 2024)
Since the digital revolution, there has been a notable increase in the use and popularity of sex toys and innovative sexual devices, which can be attributed to advancements in technology. The sex toys industry strives to improve sexual experience, pleasure and sexual health, and to address sexual dysfunction through devices and technology. With the growth of this industry, new products that are considered “smart sexual devices” have gradually entered the market. Smart sexual devices feature wireless connectivity to a smartphone application that allows the user to control the device’s features and provide personal or sexual data about their sexual experiences. Other smart devices have sensors and are able to collect physical data during usage. With the aid of this data, individuals may be able to understand their sexual behavior and arousal better, resulting in improved sexual experience or the overcoming of sexual dysfunction. The present article aims to explore the potential applications of technology-based devices, and smart sexual devices, in the treatment of male sexual dysfunctions, including premature ejaculation (PE), and delayed ejaculation (DE), as well as female sexual dysfunction (FSD), such as sexual arousal disorder and female orgasmic disorder. Furthermore, we examine the advantages and disadvantages of these devices. Given the limited literature available on this subject and the absence of controlled studies, we conduct a narrative review of the existing scientific research on technological and smart sexual devices.